Active Learning And Creative Thinking - Hasan AL-Dahlaki, Zinah AbdulAmeer; AbdulRidha AL- Tameemi, Rafid Sabah (Opción, 2019)
The research aims to know: on active learning and its importance in the educational process and creative thinking and its importance in the educational process. Active learning represents an educational philosophy that depends on the learner’s positive on the educational learning situation, and includes all educational practices and teaching procedures that aim to activate and max- imize the learner’s role, Where learning takes place through work, research and experimentation, and the learner is self-reliant in obtaining information and acquiring skills. And the formation of values and trends, it does not fo- cus on memorization and indoctrination, but rather on the development of thinking and the ability to solve problems and on teamwork and cooperative learning, and therefore the focus of active learning is not on the acquisition of information, but on the road and method by which the student acquires infor- mation and values, is a comprehensive term For a group of teaching methods that focus on placing the responsibility of learning on the learner, in principle the idea of active learning depends on the active participation of the learner in learning materials that makes him able to retrieve information better, and the concept of active learning has spread in the eighties of the twentieth century N but it has become commonplace in the nineties due to report both (Bonwell & Eison) to the American Association in 1991, which offer different methods to encourage the application of active learning.